Challenges of health services related to the population displaced by violence in Mexico - Duarte-Gómez, María Beatriz; Cuadra-Hernández, Silvia Magali; Ruiz-Rodríguez, Myriam; Arredondo, Armando; Cortés-GilI, Jesús David (Revista de Saúde Pública, 2018)
OBJECTIVE: To analyze the impacts of the care to the population displaced by violence on the health system and the challenges that this entails. METHODS: This is a narrative review of the national and international literature in PubMed, SciELO, WHO/PAHO, and Bireme. Inclusion criteria were date of publication ( from 2000), relation with the subject, and language (Spanish or English). We found 292 documents, of which 91 met the inclusion criteria. RESULTS: The main challenges are the intersectoral, participatory, and integral approach (with emphasis on mental health and sexual and reproductive health), ensured accessibility to health services, the need for a reliable registration and information system of the population displaced by violence and its characteristics, and the addressing of the biopsychosocial problems of the different groups, especially women, persons with disabilities or infectious diseases, adolescents, children, ethnic minorities, older adults and the lesbian, gay, bisexual, transsexual, and intersexual population. CONCLUSIONS: The lack of political will to accept and see the internal displacement by violence and its importance as a humanitarian and public health problem is an obstacle to the adequate and timely care of the population displaced by violence in Mexico.